Aggregate import demand and expenditure components in Japan: An empirical study - Tuck, Cheong Tang (Universiti Utara Malaysia, 2003)
This paper investigates the determinants of Japan's aggregate import demand function. In contrary with traditional specification of using single real income variable, the present study examines the various components of real income that are final consumption expenditure, domestic investment and expenditure on export goods, and relative prices. The 'bounds' testing approach in Pesaran et al. (2001), which based on estimation of unrestricted error-correction model (UECM) was used for cointegration analysis over the sample period 1973-1997. The result confirms a cointegrating relation among the quantity of import and its determinants as well as various expenditure components. The various expenditure components provide different impacts on Japan's imports volume in short run. The UECM appears to track the data well.